Restorative Justice As An Alternative To Resolving Criminal Cases Committed By Children In Conflict With The Law - Yulianto, Irwan (International Journal of Educational Research & Social Sciences, 2023)
Child protection in the criminal justice system for children, in conflict with the law in accordance with Law Number 11 of 2012 concerning the Criminal Justice System for children Crimes committed by children, is legal protection for children at the investigation, prosecution, and trial stages. The Restorative Justice approach prioritizes improving the relationship between the victim and the perpetrator of the crime. Law No. 11 of 2012 Article 9 paragraphs (1) and (2) regulate the pursuit of diversion in paragraph (1), investigators, prosecutors, and judges must consider; the category of a criminal offence, the age of the child, the results of community research from tapas; and the support of the family environment and society. Paragraph (2) Diversion agreements must obtain the consent of the victim and/or the victim's family and the willingness of the child and his/her family, except for criminal offences in the form of violations, minor criminal offences, victimless criminal offences or the value of the victim's loss is not more than the value of the minimum wage of the local provision. The forms of Diversion agreements, among others, Peace with or without compensation; handover back to parents/guardians participation in education or training in educational institutions or LPKS for a maximum of 3 (three) months; or community service.